Makna Perkataan Paulus “Menggenapkan dalam Dagingku Apa yang Kurang pada Penderitaan Kristus” menurut Kolose 1:24 - Reniati Esri Nabunome; Lea Adelia Dael; Malik Bambangan (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Suffering is a condition where a person experiences pain or difficulty in living their life. Paul's words about "fulfilling what was lacking in Christ's suffering" raise the question that whether Christ's suffering on the cross was incomplete? And it is as if Christ's suffering was ineffective and limited so that redemption had to be completed or completed through Paul's suffering. However, Christ's suffering on the Cross was perfect, sufficient to atone for human sins and did not need to be fulfilled again. The thing that needs to be accomplished or fulfilled is suffering for the sake of preaching the Gospel, about Christ who was incarnated as a human, died as a ransom sacrifice and was resurrected from the dead. So everyone can know God through His power and resurrection. This research uses descriptive qualitative methods. The purpose of this study is first to "deliver a theological answer regarding the meaning of "filling up in my flesh what is lacking in the sufferings of Christ" Second, to provide an important meaning that every believer must truly live in Christ, because the perfect redemption of Jesus Christ has been done to save mankind. The final result of the study on Colossians 1:24 provides the meaning that every believer is called to fill up what is lacking in the sufferings of Christ, namely, the suffering related to the challenges of preaching the gospel. Like Paul who was never free from suffering when preaching the gospel, but Paul remained joyful, and continued to preach the gospel. Likewise, we as believers should follow Paul's example so that the gospel can be spread throughout the face of the earth.